Development of a prototype barbeque grill using wiper motor / Muhammad Nazirul Mohd Sani - Mohd Sani, Muhammad Nazirul (2024)
Nowadays, the use of grills has become widespread. Therefore, it is not surprising that many types of barbeque grills that have their own qualities can be found on the market. However, the high cost is a barrier to ownership as its large size often contributes to high prices. This will also make it difficult to store after use. The aim of this project is to create a barbeque grill that enhances user-friendliness and durability also emphasizing ease of maintenance. The primary objective is to design a grill that employs the rotisserie method, utilizing a wiper motor to achieve uniform cooking. The advantage of using a wiper motor is that it requires a lower-voltage power supply. Studies have indicated that the environmental impact of barbecue grills is significant, primarily attributed to their extensive charcoal consumption required for uniform cooking. Additionally, the rotisserie technique is less commonly utilized in budget-friendly barbecue grills. The study found that this technique can reduce grilling time and minimize the use of excessive charcoal. The choice of materials significantly influences the product's longevity. As a result, the decision was made to predominantly utilize mild steel in this project, along with a rust-preventing finishing spray. Furthermore, product safety is a crucial factor in ensuring a product's sustainability and reducing pollution can lead to a higher-quality product. A grill that uses less fuel while still maintaining optimal cooking temperatures would be more environmentally friendly and save users money. The use of high-quality and durable materials, such as mild steel, can prevent rusting and increase the grill's resilience. Ultimately, incorporating these improvements can lead to the creation of a better BBQ grill machine that offers a safer, more efficient, and versatile cooking experience, with the added potential for commercial value